1972
DOI: 10.1063/1.1693843
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Stability of Stagnation Water Boundary Layer with Heat Transfer

Abstract: Neglecting temperature fluctuations, assuming viscosity is only temperature dependent, and assuming all other fluid properties are constant, the two-dimensional linearized parallel flow stability problem is adequately treated by modifying the Orr-Sommerfeld equation to include viscosity variations with temperature. The resulting equation is used to study the spatial stability of stagnation water boundary layer with heat transfer. The mean flow with free-stream temperature T∞ = 60°F and wall temperature Tw rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Wazzan et al [6] for water flowing over a heated flat plate, for example, found the critical Reynolds number to vary between 520 and 16000. In forced convection as well as in free convection flows the strongest effects on flow stability often come from changes in viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Wazzan et al [6] for water flowing over a heated flat plate, for example, found the critical Reynolds number to vary between 520 and 16000. In forced convection as well as in free convection flows the strongest effects on flow stability often come from changes in viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…(2) and (3) it immediately foIlows, that we have introduced T = (T* -T~)/(q~L~/k~) and p = (F -P*a)/(P~U~ 2) as dimensionless temperature and pressure, respectively. Here LR, U~, PR and T R are reference quantities, q~ is a constant heat flux across the wall.…”
Section: Asymptotic Approach; Combined Methodsmentioning
confidence: 99%
“…For a heated flat plate boundary layer in water, for example, Wazzan et al [2] found that ~e critical Reynolds number varies between 520 and nearly t6 000 (based on the displacement thickness). Thus there is a considerabIe potential for transition control with technical applications in various fieIds, see Morkovin and Reshotko [3] for a review on transition control for drag reduction.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…However, the details of the physical mechanisms by which spatial gradients in density and viscosity affect the development and concentration of turbulence structures remain poorly understood, largely because of the relatively disorganized state of the coherent turbulence structures in a fully-turbulent boundary layer (Azih et al, 2012). Conversely, studies which focus on the influence of spatial gradients in thermophysical properties on boundary layer stability are limited to using linear stability analysis and experimentally determining the point of transition in flows that are heated or cooled near standard atmospheric pressure and temperature (Wazzan et al, 1972;Özgen, 2004). In these studies, the property gradients in the boundary layer are several orders of magnitude lower than in flows which are heated at a thermodynamic state near the pseudocritical point.…”
Section: Chaptermentioning
confidence: 99%
“…The boundary layers developing on the two sides of the splitter plate merge downstream of the splitter plate forming a free shear layer. Since the initial roll-up of a free shear layer properties on flow instability have been established to be several orders of magnitude lower than those of density and viscosity (Azih and Yaras, 2013;Wazzan et al, 1972;Schäfer et al, 1995;Özgen, 2004).…”
Section: Spatial Gridmentioning
confidence: 99%